Regulation of intestinal microflora and metabolites of Penthorum chinense Pursh on alcoholic liver disease - Zhang, Hui; Cui, Xiao; Liu, Wei; Xiang, Zheng; Ye, Ji-Feng (Frontiers in Pharmacology, 2024)
Introduction: Alcoholic liver disease (ALD) was the second leading cause of liver injury. Penthorum chinense Pursh (GHC) is an important Miao ethnic drug of traditional Chinese medicine for the treatment of liver disease, but the pathogenesis is not clear. Aim of the study: To analysis the intestinal microflora and metabolic pathway of GHC on ALD mice. Methods: An HPLC-QTOF-MS method was used to identified the components from GHC extract, firstly. 60 mice were divided into six groups including blank group, model group, positive group and GHC groups (0.29, 0.87 and 2.61 g/kg). ALD mice was treated with GHC for 12 days. ALT, AST, TC and TG in serum were determined, liver index and pathological analysis were achieved. 16S rRNA gene sequencing was used to detect the intestinal microbial diversity. Finally, UPLC-QTOF-MS was used to analysis the metabolic pathways. Results: 38 ingredients were identified in GHC extract. Compared with the model group, liver index of the positive group and GHC (2.61 g/kg) group was significantly reduced. Compared with the model group, contents of ALT, AST, TC and TG of GHC groups reduced in a dose-dependent manner. Intestinal microbial diversity analysis indicated that Chao1, Observed species, Pielou_e, and Shannon indexes in GHC group (2.61 g/kg) were lower than those in model group. Principal coordinate analysis indicated that the intestinal microbial composition between blank group and model group, the model group and GHC (2.61 g/kg) group changed significantly. Compared with the model group, proportion of Firmicutes decreased, and the proportion of Bacteroidetes increased significantly in GHC group, which were 50.84% and 40.15%. The more prominent bacteria in the GHC group were odoribacteraceae, turicibacter, deferribacteraceae, and the intestinal beneficial symbiotic bacteria mucispirillum. Metabolic analysis indicated that, compared with blank group, 90 metabolites in model group changed significantly, and 68 metabolites were significantly callback in GHC group. Discussion: GHC has a therapeutic effect on ALD by regulating intestinal flora imbalance and metabolic pathways including Glycine, serine and threonine metabolism, Glutathione metabolism, Arginine and proline metabolism, Alanine, aspartate and glutamate metabolism, Butanoate metabolism and primary bile acid biosynthesis.